Venous thromboembolism : a nurse's guide to prevention and management - Welch, Ellen (Physician) (Wiley-Blackwell, 2010)
Written primarily with nurses in mind, this book provides a comprehensive overview of venous thromboembolism, a condition that rears its head regardless of specialty, killing thousands of people around the world in hospital beds and in the community alike. This book explains what it is, what symptoms to watch out for, how patients should be managed, and perhaps most importantly, how to prevent its development in those at risk. Based on the most up to date published guidelines on the subject, the book is pitched at a level appropriate for medical and nursing staff alike, covering basic pathophy.